2023
DOI: 10.1080/2162402x.2022.2163781
|View full text |Cite
|
Sign up to set email alerts
|

In vivo dynamics and anti-tumor effects of EpCAM-directed CAR T-cells against brain metastases from lung cancer

Abstract: Lung cancer patients are at risk for brain metastases and often succumb to their intracranial disease. Chimeric Antigen Receptor (CAR) T-cells emerged as a powerful cell-based immunotherapy for hematological malignancies; however, it remains unclear whether CAR T-cells represent a viable therapy for brain metastases. Here, we established a syngeneic orthotopic cerebral metastasis model in mice by combining a chronic cranial window with repetitive intracerebral two-photon laser scanning-microscopy. This approac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 41 publications
0
6
0
1
Order By: Relevance
“…EpCAM is expressed in about 50% of NSCLC tumors. 50 Similar to CEA, expression by normal cells is polarized to the luminal surface, whereas such polarity is not evident in transformed cells. Once again, however, pulmonary immunopathology has been noted in some pre-clinical models when EpCAM has been targeted using CAR T-cells.…”
Section: Epithelial Cell Adhesion Molecule (Epcam)mentioning
confidence: 99%
See 1 more Smart Citation
“…EpCAM is expressed in about 50% of NSCLC tumors. 50 Similar to CEA, expression by normal cells is polarized to the luminal surface, whereas such polarity is not evident in transformed cells. Once again, however, pulmonary immunopathology has been noted in some pre-clinical models when EpCAM has been targeted using CAR T-cells.…”
Section: Epithelial Cell Adhesion Molecule (Epcam)mentioning
confidence: 99%
“…51 Using an orthotopic Lewis lung carcinoma tumor model, Xu et al demonstrated that a 2G (CD28) CAR T-cells targeted against EpCAM could delay intracranial disease progression following local but not systemic delivery, although persistence of cells was insufficient to achieve disease eradication. 50 One strategy that may be used to dial down risk of toxicity associated with the targeting of self-antigens such as EpCAM entails the use of low affinity targeting moieties that can discriminate between healthy (EpCAM low) and malignant cells (EpCAM) high. 52 Nonetheless, risk of antigen downregulation leading to therapeutic failure needs to be considered with this approach.…”
Section: Epithelial Cell Adhesion Molecule (Epcam)mentioning
confidence: 99%
“…Adoptive transfer of peripheral blood lymphocytes (PBL) transduced with an EpCAM-specific CAR prevented metastasis of prostate cancer PC3 cells and significantly reduced tumor growth of PC3M cells in nonobese diabetic/severe combined immunodeficiency (NOD/SCID) mice [104]. A recent publication examined the ability of anti-EpCAM CAR-T cells to prevent lung cancer brain metastasis [105]. While intraparenchymal injection of anti-EpCAM CAR-T cells reduced LL/2 tumor growth in the brain in vivo, intravenous administration of the CAR-T cells failed to accumulate within the tumor and, in both cases, failed to persist within the tumor, suggesting that the success of CAR-T cells may be cancer-and location-specific [105].…”
Section: Car-t Therapiesmentioning
confidence: 99%
“…Xu et al [ 203 ] explored the effect of application methods on the performance of CAR-T cells in treating lung cancer BM and concluded that, compared to intravenous injection, local application of EpCAM-CAR-T cells achieved a more significant accumulation in the target tumor and significantly stimulated antitumor effects without causing central nervous system or systemic off-target toxicity. Nevertheless, the researchers found that CAR-T cells lacked sufficient persistence in tumor aggregation and failed to consistently exert tumor cell killing effects.…”
Section: Immunotherapy Targeting the Tmementioning
confidence: 99%